The Voice of the People : Public Opinion in Pakistan 2007-2009 - Edited by Gilani, Ijaz Shafi (Karachi Oxford University Press, 2010)
The purpose of this book is to meaningfully discuss what Pakistanis thought as a collectivity about various local and international issues during 2007-08. Voice of the People covers a diverse range of subjects from democracy, war on terror, to religious inclinations and consumption preferences. Furthermore, it dispels various fallacies about public behavior, for example misconceptions that since the Pakistani public is largely illiterate it is incapable of understanding the complexities of governance or judicious foreign policies, that it approves of wholesale violence in the name of religion, that it is unaware of global climatic changes and is hardly bothered about issues beyond basic necessities. Careful analysis of the data disproves or qualifies these misconceptions which flourish because measuring popular opinion is difficult while passing off unsubstantiated generalizations about an amorphous entity is easy.
Include Tables and Index.
Keywords: Public opinion -- Pakistan -- Politics and government--Public opinion -- Economic history--Public opinion